MATERIAL AND TECHNICAL BASIS OF THE MANAGEMENT OF THE ACTIVITY OF INSPECTORS OF WOMEN'S ISSUES OF INTERNAL AFFAIRS BODIES (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2024)
Abstract: this thesis analyzes the material and technical bases of the management ofthe activities of inspectors of internal affairs bodies on women's issues. In order to protectthe rights of women, prevent violence against them and ensure equality in society, thework carried out by inspectors should be provided with modern material and technicalresources. The material and technical base, including the necessary devices, specialists,covers training and methodical materials. This study also discusses the legal framework,the general culture in the community, and the necessary strategies to improve theeffectiveness of inspectors.